Spirituality and healthcare: Towards holistic people-centred healthcare in South Africa - Porte, Andre de la (HTS teologiese studies, 2016)
Healthcare in South Africa is in a crisis. Problems with infrastructure, management, human resources and the supply of essential medicines are at a critical level. This is compounded by a high burden of disease and disparity in levels of service delivery, particularly between public and private healthcare. The government has put ambitious plans in place, which are part of the National Development Plan to ward 2030. In the midst of this we find the individual person and their family and community staggering under the suffering caused by disease, poverty, crime and violence. There is a more than 70% chance that this person and their family and community are trying to make sense of this within a spiritual framework and that they belong to a faith-based community. This article explores the valuable contribution of spirituality, spiritual and pastoral work, the faith-based community (FBC) and faith-based organisations (FBOs) to holistic people-centred healthcare in South Africa.Keywords: Healthcare; Spirituality; Clinical Spiritual Counselling